Environmental Monitoring for Enteroviruses in Maputo, Mozambique—2018 - Diocreciano Matias Bero; Sheila António Nhassengo; Ivanildo Pedro Sousa; Silas Oliveira de Sousa; Raiana Scerni Machado; Amanda Meireles Nunes Dias; Cristiane de Sousa Ferreira; Fernanda Marcicano Burlandy; Nilsa de Deus; Edson Elias da Silva (Pathogens, 2022)
Due to the possibility of wild poliovirus importation from endemic regions and the high circulation of vaccine-derived poliovirus type 2 in the African region, Mozambique implemented a surveillance program to monitor the circulation of enteroviruses in the environment. From January to November 2018, a period that immediately preceded the cVDPV outbreak in Africa, 63 wastewater samples were collected from different areas in Maputo city. A total of 25 samples (39.7%) were positive based on cell culture isolation. Non-polio enteroviruses were found in 24 samples (24/25; 96%), whereas 1 Sabin-related poliovirus was isolated. Neither wild nor vaccine-derived poliovirus was detected. High circulation of EVB species was detected. Environmental surveillance in the One Health approach, if effectively applied as support to acute flaccid paralysis, can be a powerful aid to the public health system to monitor poliovirus besides non-polio enteroviruses in polio-free areas.